Literature Study of Lactic Acid Bacteria in Bangka Belitung: Sources, Methodology, Utilization, And Identification - Rahmad Lingga; Rinny Saputri; Fitriyani Fitriyani; Muhammad Panca Indra (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Bangka Belitung has various types of fermented foods, in the production of which lactic acid bacteria are involved. Lactic acid bacteria plays important role in enhancing the nutritional value of food ingredients, extending their shelf life, producing distinct aromas, and preventing contamination from pathogenic bacteria. Additionally, lactic acid bacteria can also act as probiotics for application in livestock or fisheries. This article examined several studies on lactic acid bacteria that were linked to the biological resources of Bangka Belitung. The aspects studied included the sources of lactic acid bacterial isolates, research methods or approaches employed, utilization, and identification of lactic acid bacteria. Most of the research related to lactic acid bacteria has been conducted on fermented foods, primarily 'rusip,' which is a fermented food product made from shrimp or fish. This review expected to provide an overview of the trends and research interest in lactic acid bacteria conducted in Bangka Belitung, while also mapping out aspects that need further exploration in subsequent research